Pathogenicity and characteristics of spodoptera litura nucleopolyhedrovirus from Peninsular Malaysia - Sajap, Ahmad Said; Kotulai, James R.; Abdul Bakir, Mohammad; Lau, Wei Hong; Abdul Samad, Norani; Abdul Kadir, Hussan (Universiti Putra Malaysia Press, 2000)
A study on the characteristics of the Spodoptera litura nucleopolyhredovirus (SpltNPV) was carned out. The result shows that the virus was pathogenic and specific to its host, S. litura larva. It caused 96% larval mortality within a period of 10 days at a dosage of 6 x 1(jS PIBs/larva and did not affect lepidopteran larvae, Spirama retorta Clerck (Noctuidae) and bagworm, Pteroma pendulaJoannis (Psychidae). The polyhedra, varied in their shape, contained many virions with more than one nucleocapsid in a virion.